2013
DOI: 10.1097/hcr.0b013e318283927f
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Mortality 12 Years After an Acute Cardiac Event

Abstract: Mild inhospital depression and moderate/severe 2-month depression were predictive of 12-year deaths. The findings suggest a prognostic benefit in undertaking repeat depression screening 2 months after an acute cardiac event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The negative health impacts appear to surface or increase when anxiety or depressive symptoms persist or emerge after hospital discharge during convalescence (Blumenthal et al, 2003;Murphy et al, 2013;Worcester et al, 2019;Kim et al, 2020). In a 12-year follow-up study of 170 female AMI and CABGS patients, we found that the mortality rate was highest in those whose depression symptoms worsened in the 2 months after hospital discharge, and lowest in those whose inhospital symptoms remitted by 2 months (Murphy et al, 2013). Others have reported similar findings (Blumenthal et al, 2003).…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…The negative health impacts appear to surface or increase when anxiety or depressive symptoms persist or emerge after hospital discharge during convalescence (Blumenthal et al, 2003;Murphy et al, 2013;Worcester et al, 2019;Kim et al, 2020). In a 12-year follow-up study of 170 female AMI and CABGS patients, we found that the mortality rate was highest in those whose depression symptoms worsened in the 2 months after hospital discharge, and lowest in those whose inhospital symptoms remitted by 2 months (Murphy et al, 2013). Others have reported similar findings (Blumenthal et al, 2003).…”
Section: Introductionsupporting
confidence: 63%
“…It is generally agreed that around one in five patients meet diagnostic criteria for depression while hospitalized for a cardiac event (Thombs et al, 2006;Lichtman et al, 2008;Colquhoun et al, 2013;Murphy et al, 2016), and up to one in three experience severe anxiety (Andrew et al, 2000;Tully and Baker, 2012;Murphy et al, 2016). While relatively few studies have reported rates of anxiety and depression at later points during patients' convalescence, there is evidence that early symptoms resolve for many patients during the first few months after hospital discharge (Murphy et al, 2008a(Murphy et al, , 2013(Murphy et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal levels of pre-CABG depression are observed, although other studies have indicated higher levels, from moderate to severe [92]. However, more than 25% of patients with normal levels are at risk of worsening, for which reason continuous reassessment can identify patients with transient symptoms of depression [93].…”
Section: Discussionmentioning
confidence: 97%
“…Some authors report that more than 50% of patients were receiving medical treatment for depression, even though they had no symptoms of depression [106]. For this reason, the use of measurement tools to confirm the presence and levels of depression makes it possible to identify the at-risk patients, and therefore carry out a more in-depth post-CABG follow-up, of at least nine months [93].…”
Section: Discussionmentioning
confidence: 99%